Consumptive Credit Accounting Information System Design at PT. Metro - Mardiana, Mardiana (Journal of Economics and Business (JECOMBI), 2022)
This research is motivated by the problem of low performance of a company at PT. METRO is a credit sales technique for customers who process payment data, so data processing takes a long time. Therefore, with the implementation of the Consumptive Credit Accounting Information System application that has been designed, in the form of reports that can be presented quickly such as customer reports, credit payments and suppliers. Each system is designed to provide supervision and convenience for all transactions carried out by a company so that a company's performance runs effectively and efficiently.